Integrating Neuro-Linguistic Programming And Multiple Intelligences In Language Learning: A Bridge Between Theory And Practice - Asiqur Rahaman; Dr. Pragyan Paramita Pattnaik (Educational Administration: Theory and Practice, 2024)
This research delves into the benefits of combining Neuro Linguistic Programming (NLP) and Multiple Intelligences (MI) in language learning. NLP utilizes language, behavior and strategic thinking to improve communication and learning while MI theory identifies eight types of intelligence fostered by tailored learning environments. The study extensively reviews existing literature, on NLP and MI focusing on the possibilities and obstacles of integrating them into language education. It demonstrates how the fusion of NLP and MI can establish learning settings that cater to learning preferences. This research contributes to the field of language learning by connecting theory with applications. Through the use of SPSS software for data analysis it examines hypotheses, investigates relationships between variables. The results indicate that incorporating NLP and MI in language learning shows potential for addressing differences and preferences ultimately improving outcomes, for learners and educators in a language learning setting